ANALYSIS OF CHANGES IN LAND USE IN 2005 UNTIL 2015 IN THE PENIRAMAN VILLAGE SUNGAI PINYUH SUBDISTRICT MEMPAWAH DISTRICT - SANJAYA, PANDI; Ir. H. Riduansyah, MP, Ir. H. Riduansyah, MP; Ari Krisno Hadi, SP., M.Si, Ari Krisno Hadi, SP., M.Si (Fakultas Pertanian Universitas Tanjungpura, 2017)
ABSTRACT The rapid population growth requires increasing number of residential areas and for land use conversion on agricultural production. This study aims to Know extensive changes in land use in 2005 and 2015, Knowing paddy land-use changes in 2005 and 2015 as well as land use change Assessing the level of rice production as well as reference information to calculate an estimate of rice production. This research was conducted in the village of Peniraman, Subdistrict Sungai Pinyuh, Subdistrict Mempawah, West Kalimantan Province. The duration of the study period commencing from April 16 2016 until May 16 2016. The shomed that in 2015 dominate land use plantation, (1665.31 ha), or 64.55% of the area of